The next frontier of restaurant management : harnessing data to improve guest service and enhance the employee experience - Susskind, Alex M.; Maynard, Mark, 1967- (Cornell hospitality management., 2019)
"Provides managers, employees, and students with tools to better understand the complexities of the restaurant business and how to use those tools to improve business operations"--